Własności dominacji dla zmiennych dwuwymiarowych - Pańczyk, Magdalena (Stochastic Dominance Rules - Bivariate Random Variable, 2007)
After the publication of the stochastic ordering research efforts have been made directed wards to generalizing these rules to multivariate case. In this paper we describe stochastic orderings, especially model of mean - variance and stochastic dominance - the one-attribute case. In the next step, we generalize these results to two-attribute cases. We define moments for bivariate random variable and describe analogous to mean-variance orders. We define stochastic dominance rules for marginalizations, later we define bivariate stochastic ordering, especially in the context of probability inequalities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 195-205